AYUNAN FOUCOULT UNTUK MENENTUKAN GARIS LINTANG KOTA SURABAYA - G. Budijanto Untung (Magister Scientiae, 2017)
Foucault pendulum experiment was conducted at the Physics Laboratory of Widya Mandala Catholic University Surabaya. The goal of the experiment was to measure the latitude of Surabaya. The experimental results showed that the latitude of Surabaya was in the interval of 8.43o S and 8.57o S with relative error of 0.85%. Comparing these values with the reference data, it was found out that the latitude of Surabaya is in the interval of 7.15 S and 7.35o S. The deviation of the experimental results from the reference values was around 14.7%. The main source of the deviation was the angle precision measurement of the device.